INTEGRASI ELEMEN SOCIAL EMOTIONAL LEARNING (SEL) DALAM PROSES PRODUKSI PERIKANAN AIR TAWAR DI TEACHING FACTORY SMK DZAKIYYUN CIANJUR - Aang Ali Nurzen Amin; Anton Musa; Mohammad Dzakiyyuddin; Ansori; Emas Sahribanon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the integration of Social Emotional Learning (SEL) elements into freshwater aquaculture production within the Teaching Factory (TEFA) model at SMK Dzakiyyun Cianjur. Employing a qualitative case study approach, data were collected through participatory observation, in-depth interviews, and document analysis involving productive teachers, industrial instructors, and students directly engaged in the production cycle. The findings indicate that SEL competencies are embedded in all stages of the TEFA workflow with different emphases on self-management, responsible decision-making, social awareness, and relationship skills. Furthermore, the role of teachers has shifted from technical instructors to emotional coaches through the consistent mechanism of briefing–action–debriefing and authentic assessment of soft skills. The integration of SEL noticeably strengthened students’ engagement, self-initiative, and team collaboration under pressured work conditions. This research provides new insights into vocational education by demonstrating that embedding SEL within TEFA constitutes an effective strategy to reduce soft-skill gaps among vocational graduates and enhance holistic job readiness in the context of modern freshwater aquaculture industries.